Ultrasonography-Guided Muscle Hematoma Evacuation - Pia Kareena Quiñones, M.D.; Soichi Hattori, M.D.; Shin Yamada, M.D.; Yuki Kato, M.D., Ph.D.; Hiroshi Ohuchi, M.D., Ph.D. (Arthroscopy Techniques, 2019)
Muscle injuries commonly occur in athletes, and in severe cases, they can result in hematoma formation, leading to pain and loss of function. A technique for minimally invasive ultrasound-guided evacuation of muscle hematoma is presented. A simple and quick outpatient procedure done under local anesthesia for faster muscle recovery provided immediate decompression of the muscle compartment, leading to early return to play.